Enhanced plasticity by deformation-induced nanocrysallization in bulk amorphous Al2O3-ZrO2-Y2O3. Issue 3 (15th February 2017) - Xu, Xiqing; Zhai, Chenxi; Ren, Haitao; Guo, Linlin; Hou, Feng; Liu, Jiachen
Abstract: Deformation of bulk amorphous Al2 O3 -ZrO2 with different ratios of A/Z was investigated under compression at 500 °C. A20Z and A40Z exhibited brittle fracture and remained amorphous after compression; however, significant plastic deformation was achieved in A60Z and A80Z. Nanocrystallite of t -ZrO2 were detected in A60Z and A80Z during the plastic deformation, and deformation-induced nanocrystallization in amorphous oxides was reported for the first time. Ductile transformation temperature was proposed as a criterion for the deformability of amorphous materials. The nanocrystallization improved the plasticity in turn, due to the easier formation of multiple shear bands at the interface between nanocrystallite and amorphous matrix. Crystallization activation energy was identified as a key factor dominating the deformation of amorphous oxides, and low crystallization activation energy could contribute to easy nanocrystallization, lower the ductile transformation temperature, and promote the plasticity. This work gave further understanding of plastic deformation in amorphous oxides.